Pengaruh Persepsi Manfaat dan Persepsi Kemudahan Terhadap Minat Penggunaan E-wallet Gopay di wilayah DKI Jakarta - Ramadhan, Alan; Tamba, Rousdy Safari (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to determine the influence of perceived benefits and perceived convenience on interest in using the Gopay e-wallet in the DKI Jakarta area. Data was collected through the distribution of questionnaires that have been tested for validity and reliability. The results showed that the influence of perceived benefits on interest in using the Gopay e-wallet was 71,1%, and the effect of perceived convenience on interest in using the GoPay e- wallet was 61,1%. This means that perceived benefits and perceived convenience have a significant effect on the interest in using the GoPay e- wallet in the DKI Jakarta area.